Comparison of laboratory test performance between asphalt-rubber hot mix and dense graded asphalt concrete - Sousa, Jorge B. (2000)
"Reflective cracking in pavements : research in practice" contains the Proceedings of the 4th International RILEM Conference on Reflective Cracking in Pavements (Proceedings PRO11).